(untitled) (Economics and region, 2020)
The article considers various aspects of the impact of the COVID-19 pandemic on the economic sphere of the countries of the European region. They write about some specific approaches to the government’s influence on leveling the negative consequences of the spread of the pandemic within countries. The authors conclude that COVID-19 hurts the level of trust in society and the degree of confidence in consumer sentiment. Simultaneously, unforeseen events such as COVID-19 stimulate the emergence and accelerated introduction of new technologies. It is further generalized that Ukraine must take into account all global trends in the implementation of economic measures, as well as follow the mainstream of technologies that are increasingly widespread in society, in particular the concept of welfare economics.